A Critical Analysis of the Indonesian Human Rights Action Plan 1998-2020 - Majda El Muhtaj (Jurnal HAM, 2022)
This article examines the genesis and evolution of Indonesia's National Human Rights Action Plan (NHRAP), known as Rencana Aksi Nasional Hak Asasi Manusia (Ranham), throughout the Reform era from 1998 to 2020. Ranham stands as an important national policy document designed to articulate two primary objectives: first, to delineate how the state integrates human rights principles and norms into its policies; and second, to establish benchmarks for measuring its notable achievements in this domain. Adopted and implemented by successive Indonesian governments, Ranham has been instituted through Presidential Regulations across five distinct phases over two decades of the Reform era. The foundation of Ranham can be traced back to the Vienna Declaration and Program of Action (VDPA) of 1993, a seminal international human rights framework. Currently, over 70 countries, Indonesia among them, have formulated their respective versions of Ranham. This article underscores Ranham's role as a manifestation of Indonesia's commitment to advancing the human rights agenda nationally. However, it also identifies a significant challenge: the insufficient conceptualization of human rights, which hampers the robust development and fortification of Indonesia's national human rights framework.